Different patterns of endocytosis in cochlear inner and outer hair cells of mice - Li, Sijun; Yu, Shukui; Ding, Tonghui; Yan, Aihui; Qi, Yue; Gong, Shusheng; Tang, Siquan; Liu, Ke (Physiological research, 2019)
Precise and efficient endocytosis is critical for sustained neurotransmission during continuous neuronal activity. Endocytosis is a prerequisite for maintaining the auditory function. However, the differences between the patterns of endocytosis in cochlear inner hair cells (IHCs) and outer hair cells (OHCs) remain unclear. Both IHCs and OHCs were obtained from adult C57 mice. Patterns of endocytosis in cells were estimated by analyzing the uptake of FM1-43, a fluorescent. The observations were made using live confocal imaging, fluorescence intensities were calculated statistically. Results revealed the details about following phenomenon, i) sites of entry: the FM1-43 dye was found to enter IHC at the apical area initially, the additional sites of entry were then found at basolateral membrane of the cells, The entry of the dye into OHCs initially appeared to be occurring around whole apical membranes area, which then diffused towards the other membrane surface of the cells, ii) capacity of endocytosis: fluorescence intensity in IHCs showed significantly higher than that of OHCs (P<0.01). We have found different patterns of endocytosis between IHCs and OHCs, this indicated functional distinctions between them. Moreover, FM1-43 dye can be potentially used as an indicator of the functional loss or repair of cochlear hair cells.
Keywords: pyridinové sloučeniny; vnitřní vláskové buňky; Hair Cells, Auditory, Outer; Pyridinium Compounds; Organ Culture Techniques; orgánové kultury - kultivační techniky; sluchové evokované potenciály; Endocytosis; zvířata; myši; Hair Cells, Auditory, Inner; myši inbrední C57BL; endocytóza; Mice; biologický transport; fluorescenční barviva; Fluorescent Dyes; Mice, Inbred C57BL; Evoked Potentials, Auditory; kvartérní amoniové sloučeniny; Quaternary Ammonium Compounds; Animals; vnější vláskové buňky; Biological Transport